Macroporous structures based on biodegradable polymers—candidates for biomedical application. Issue 9 (20th February 2013) - Simionescu, Bogdan C.; Neamtu, Andrei; Balhui, Ciprian; Danciu, Mihai; Ivanov, Daniela; David, Geta
Abstract : New hybrid cryogels comprising natural polymers (free atelocollagen or atelocollagen mixed with a hyaluronic acid derivative) and a synthetic polyester—poly(ε‐caprolactone)—were successfully developed by a cryogenic treatment and a subsequent freeze‐drying step. Systematic studies on the effect of preparation conditions (reaction mixture composition, total concentration of the feed dispersion, and freezing regime) on cryogelation efficiency were conducted. The degree of cross‐linking and the morphology of the obtained materials were analyzed using differential scanning calorimetry (DSC), Fourier transform infrared spectroscopy (FTIR) and (environmental) scanning electron microscopy (ESEM/SEM) techniques. Considering their possible biomedical application, the developed macroporous hydrogels were also investigated in terms of swelling behavior and hemo/biocompatibility. The produced hydrogels had an uniform interconnected open porous structure with a porosity of up to 95% and pores size in the range of 83–260 μm. All obtained cryogels were elastic, mechanically stable, with a superfast swelling kinetics. In vitro hemocompatibility assay gave hemolysis ratios (HRs) lower than 0.5%, which is below the permissible limit of 5%. The in vivo tolerance tests performed by implantation of cryogel specimens into Wistar rats proved their biocompatibility. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 2689–2698, 2013.